Analisis Forecasting Penjualan Produk Perusahaan - Jonnius Jonnius; Auzar Ali (Lembaga penelitian dan pengabdian kepada masyrakat, 2012)
Forecasting for a company is an important thing to do in order to estimate the demand for marketed products as well as the estimated amount of supplies needed for the coming period. In doing forecasting needs to consider appropriate methods to obtain maximum results. Not all methods are appropriate to be used for forecasting sales of various products. One of the method that can be used is the exponential smoothing method, as was done in forecasting sales of commercial vehicles on the PT. Suka Fajar Ltd Bangkinang. Sales forecasting methods can be selected for commercial car type T120 SS PU is the double exponential smoothing method, whereas for PU type L300 and FE 74 can use a triple exponential smoothing method. These two methods are selected following the shape of the trend of the past sales data for each type of product.